Optimization of Employee Performance - Tahara, Anisa; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This research aims to see the influence between variables and the title Influence of Organizational Culture on Employee Performance Through Work Motivation as an Intervening Variable at the Bpjs Employment Sumbagut Regional Office, Case Study at the Tanjung Morawa and Pematang Siantar Branches. The type of research used is quantitative, this research was conducted on Jl. Sakti Lubis No. 5 Timbang Galung, Pematang Siantar City and Tanjung Morawa Branch Office: Jl. Raya Medan Tanjung Morawa KM 14.5 Bangun Sari Baru Village, Bangun Sari Baru, Kec. Tj. Morawa, Deli Serdang Regency, North Sumatra. The population of this study was 65 employees and the sample of this study was 65 and used a saturated sampling technique. Primary data sources are research data sources and questionnaires are data collection techniques. Phat analysis is a research model. The results of this research are as follows: Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.881 and a P value of 0.000 <0.05. Organizational culture has a positive and significant effect on work motivation with an original sample value of 0.686 and a P value of 0.000 <0.05. Work Motivation has a positive and insignificant effect on Employee Performance with an original sample value of 0.064 and a P value of 0.189. Organizational culture has a positive but not significant indirect effect on employee performance through work motivation with an original sample value of 0.044 and a P value of 0.194.